Determinants of Shares Prices of Plantation Companies Listed In Indonesia Sharia Stock Index (Issi) Before, During And After The Covid-19 Pandemic - Fransisca Maulida Chasanah; Sutan Emir Hidayat; Indra Indra (Department Islamic Economics, 2023)
The purpose of this study is to analyze the effect of the variables to be discussed, namely Islamic banking financing, inflation, exchange rates, and world palm oil commodity prices on the stock prices of plantation companies listed on the Indonesia Sharia Stock Index (ISSI) before, when, and after the COVID-19 pandemic. This research uses a quantitative approach, using an explanatory research design to test the hypothesis of the relationship between variables. The data that has been collected is then processed and analyzed quantitatively using the SPSS program. To test the hypothesis that has been formulated in this research, multiple linear regression method are used on time series data using the SPSS program. Based on the results of the t test research, it shows that partially Islamic banking financing, inflation, exchange rates, and world palm oil commodity prices have a significant effect on the share prices of plantation companies listed on the Indonesia Sharia Stock Index (ISSI). The results of the F test research show that simultaneously Islamic banking financing, inflation, exchange rates, and world palm oil commodity prices have a significant effect on the share prices of plantation companies listed on the Indonesia Sharia Stock Index (ISSI). The coefficient of determination (R2) of this research is 0.842, where these results indicate that variations in the share prices of plantation companies listed on the Indonesia Sharia Stock Index (ISSI) can be explained by Islamic banking financing, inflation, exchange rates, and world palm oil commodity prices, namely with a value of 0.842 or 84.2%. Meanwhile, the remaining 15.8% is explained by other variables outside the research variables. This research focuses on analyzing the variables of sharia banking financing, inflation, exchange rates, and world palm oil commodity prices, and their influence on the share prices of plantations listed on the Indonesia Sharia Stock Index (ISSI). Another limitation of this research is in terms of time, because this research will use a time period from January 2015 to June 2023, where this time period is expected to describe the state of the variables studied before, during and after the COVID- 19 pandemic. It is hoped that this research can help the government evaluate the policies implemented, and not ignore the negative impacts resulting from each policy made. Of course, it's nothing other than just for better conditions in the future. Apart from that, it is hoped that this research will provide benefits for companies, especially in the plantation sector, so that they can attract investors.